Green policies and leadership character: integrating pancasila, astha brata, and nature-inspired principles for sustainable futures - Fitriani, Arbania; Situmorang, Dominikus David Biondi; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
This study explores character-centric leadership, focusing on Pancasila and Astha Brata principles, to address global challenges like climate change. Using Kevin Cashman’s